2023
DOI: 10.1186/s40538-022-00377-1
|View full text |Cite
|
Sign up to set email alerts
|

Application of carrot waste extract and Lactobacillus plantarum in Alyssum homalocarpum seed gum-alginate beads to create a functional synbiotic yogurt

Abstract: One of the most recent and effective methods, which is currently receiving special attention and is being developed by numerous researchers, is production of microspheres from the probiotic cells. The largest market segment for functional foods is represented by dairy products, which have been touted as the most effective carriers of nutrients, such as probiotics, prebiotics, proteins, vitamins, and minerals. Yogurt is fermented dairy product that is popular all over the world. A new functional symbiotic yogur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…Bandyopadhyay et al ( 48 ) confirm the decrease in pH of carrot paste samples over 20 days of storage. Sharifi et al ( 15 ) confirmed a pH decrease and acidity increase for yogurt samples with carrot extract for 28 days. In acid-fermented products the amount of acid increases during the storage period, which is called excessive acidification or subsequent acidification, which is caused by the enzyme β-galactosidase which remains at 0–5°C.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Bandyopadhyay et al ( 48 ) confirm the decrease in pH of carrot paste samples over 20 days of storage. Sharifi et al ( 15 ) confirmed a pH decrease and acidity increase for yogurt samples with carrot extract for 28 days. In acid-fermented products the amount of acid increases during the storage period, which is called excessive acidification or subsequent acidification, which is caused by the enzyme β-galactosidase which remains at 0–5°C.…”
Section: Resultsmentioning
confidence: 94%
“…Since the supplemented samples are more acidic than the control sample, the effect of adding carrot and potato peel is seen. Because there are no phenolic antimicrobial compounds in processed cheese containing carrot and potato peel their acidity has increased to a lesser extent than in plain cheese ( 15 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Texture is one of the main characteristics in foods that affects consumer acceptance [ 58 , 59 ]. The results showed that there was a significant difference in the hardness of the ice cream texture in different treatments (p < 0.05) and it increased from 1825.063 g to 2874.316 g by increase in the concentration of dried persimmon peel powder (0–3 %wt) in ice cream formulation ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%